2005
DOI: 10.1097/01.bcr.0000185455.81677.a2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Short-Term, Intensive Social Skills Training Program for Burned Adolescents

Abstract: This study examined the efficacy of an intensive, short-term social skills training program in improving the psychosocial adjustment of burned adolescents. Sixty-four adolescents who had suffered a burn injury 2 years previously or longer and who were identified as having psychosocial difficulties (elevated behavioral problems and/or diminished competence) were assigned randomly to receive the treatment intervention or to serve as controls (32 in each group). The intervention was a social skills training curri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 14 publications
3
75
0
2
Order By: Relevance
“…In support of this, researchers have argued that those with a visible difference and higher levels of social skills experience more positive social interactions (Rumsey, Bull & Gahagen 1986;Blakeney et al, 2005). The current study's findings and previous research suggest healthcare professionals and support organisations should ensure that social skills training that specifically incorporates the needs of older adults, is available and accessible.…”
Section: Discussionsupporting
confidence: 50%
“…In support of this, researchers have argued that those with a visible difference and higher levels of social skills experience more positive social interactions (Rumsey, Bull & Gahagen 1986;Blakeney et al, 2005). The current study's findings and previous research suggest healthcare professionals and support organisations should ensure that social skills training that specifically incorporates the needs of older adults, is available and accessible.…”
Section: Discussionsupporting
confidence: 50%
“…Robinson et al [51] reported that participation in a 2-day Changing Faces workshop was associated with improved overall anxiety and social anxiety 6 months later among 64 patients with a variety of facial disfigurement types, although there was no control group. Recently, Blakeney et al [53] adapted the Changing Faces workshop social skills curriculum to develop a 4-day workshop program for adolescent burn survivors who had been burned at least 2 years previously. Adolescents who attended the workshop program showed somewhat more improvement in behavioral and emotional variables compared to a control group 1 year later.…”
Section: Discussionmentioning
confidence: 99%
“…Peer support is widely recognized to be a potent factor in positive adjustment for teenagers with a visible difference (see, for example, Blakeney et al [25]), but establishing supportive relationships with peers can prove challenging. Joining an acceptable social grouping can be particularly hard if social confidence has been eroded, for example as a result of prior teasing about appearance.…”
Section: Friendships and Relationshipsmentioning
confidence: 99%
“…Some may become defensive and socially avoidant, or may limit their social groups to one or two peers with whom they feel safe [34]. Blakeney et al [25] reported that in the region of 40-50% of burned children and adolescents demonstrate a lack of social competence which can significantly impair their psychosocial wellbeing. Once relationships have been established, concerns about the visible difference may cause ongoing difficulties, for example in developing intimate relationships.…”
Section: Friendships and Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation